Dependability in Electronic Systems Mitigation of Hardware Failures, Soft Errors, and Electro-Magnetic Disturbances - Kanekawa, Nobuyasu; Ibe, Eishi H.; Suga, Takashi; Uematsu, Yutaka; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Dependability in Electronic Systems: Mitigation of Hardware Failures, Soft Errors, and Electro-Magnetic Disturbances by: Nobuyasu Kanekawa Eishi H. Ibe Takashi Suga Yutaka Uematsu The importance of “dependability” in electronic systems is obvious, especially in safety-critical or mission-critical applications. Dependability hinges on matters such as failure causes and countermeasures for soft/hard -errors in semiconductor devices, electro-magnetic interferences, power integration, and system architecture. This book covers the practical application of dependable electronic systems in real industry, such as space, train control and automotive control systems, and network servers/routers. The impact from intermittent errors caused by environmental radiation (neutrons and alpha particles) and EMI (Electro-Magnetic Interference) are introduced together with their most advanced countermeasures. Power Integration is included as one of the most important bases of dependability in electronic systems. Fundamental technical background is provided, along with practical design examples. Readers will obtain an overall picture of dependability from failure causes to countermeasures for their relevant systems or products, and therefore, will be able to select the best choice for maximum dependability. •Provides a set of valuable techniques to design dependability into embedded systems; •Offers fault mitigation techniques widely applicable in general control systems in space and ground-based transportation systems; •Presents fundamentals of soft-errors in semiconductor devices and their impacts and countermeasures in electronic systems such as network servers and routers; •Describes fundamentals of electro-magnetic interference and practical countermeasures in many industrial applications; •Discusses vulnerability in power supply systems and how power integration is accomplished.
Introduction -- Terrestrial Neutron-Induced Failures in Semiconductor Devices and Relevant Systems -- Electromagnetic Compatibility; Power Integrity -- Dependable System Technology.
Keywords: Electronic circuits; Computer-aided engineering; Circuits and Systems; Computer-Aided Engineering (CAD, CAE) and Design